Czech gender linguistics: Topics, attitudes, perspectives - Vít Kolek; Jana Valdrová (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2020)
The aim of the present article is to analyse the existing publications dealing with Czech gender linguistics, and attitudes of their authors. Firstly, the authors of the article present an overview of the development of the discipline, beginning with its rejection to today’s acceptance. They then deal with the various ways to label people with regard to gender, and consider the formation of nouns labelling women as one of the strategies to make women visible in the language. The authors also inform readers about the psycholinguistic testing of the “generic” masculine in the Czech language and about the possibilities of Czech gender-fair language. The authors discuss the proper names of persons from the perspective of gender and personal identities, while they briefly mention translatology publications which reflect the gender perspective. Additionally, the authors present a call for further research in certain areas.